An Analysis of Complex-Valued Periodic Solution of a Delayed Discontinuous Neural Networks (Journal of Mathematical Study, 2021)
In this paper, we investigate global stability of complex-valued periodic solutionof a delayed discontinuous neural networks. By employing discontinuous, nondecreasingand bounded properties of activation, we analyzed exponential stabilityof state trajectory and $L^1$−exponential convergence of output solution for complex-valueddelayed networks. Meanwhile, we applied to complex-valued discontinuousneural networks with periodic coefficients. The new results depend on $M$−matrices ofreal and imaginary parts and hence can include ones of real-valued neural networks.An illustrative example is given to show the effectiveness of our theoretical results.